Pendidikan Berbasis Budaya Lokal dalam Hidden Curriculum: Strategi Membangun Toleransi dan Perdamaian di Sekolah Menengah Maluku - Simona Christina Henderika Litaay; Feky M. L. Manuputty; Afdhal Afdhal; Nathalia Debby Makaruku (Society, 2025)
This study examines how local cultural values are integrated into the hidden curriculum to promote tolerance and peace in secondary schools in Maluku. It investigates the influence of traditions such as Pela, Gandong, Famili, Badati, Masohi, and Ma’anu, which are not formally included in the curriculum but play a crucial role in shaping students’ social behavior and fostering inclusive learning environments. Using a qualitative case study approach, the research provides a contextualized analysis of how these cultural values function within school settings. Data were gathered through observations and in-depth interviews with teachers and students. The findings highlight the significant role of local cultural values in fostering tolerance and peace. Pela and Gandong reinforce interfaith solidarity through collaborative student activities, while the concept of Famili cultivates a sense of belonging and mutual respect. Badati and Masohi promote cooperation through project-based learning, and Ma’anu encourages an appreciation for diversity. These findings suggest that a hidden curriculum rooted in local culture can strengthen social harmony in pluralistic school environments. Beyond Maluku, this study offers insights into how culturally embedded hidden curricula can inform inclusive educational policies and curriculum design, providing a framework for other diverse and conflict-prone regions. The research underscores the importance of integrating local cultural wisdom into education as a pathway to sustainable peacebuilding.